The Control of the Specificity of CD4 T Cell Responses: Thresholds, Breakpoints, and Ceilings - Sant, Andrea J.; Chaves, Francisco A.; Leddon, Scott A.; Tung, Jacqueline (Frontiers in Immunology, 2013)
It has been known for over 25 years that CD4 T cell responses are restricted to a finite number of peptide epitopes within pathogens or protein vaccines. These selected peptide epitopes are termed “immunodominant”. Other peptides within the antigen that can bind to host MHC molecules and recruit CD4 T cells as single peptides are termed “cryptic” because they fail to induce responses when expressed in complex proteins or when in competition with other peptides during the immune response. In the last decade, our laboratory has evaluated the mechanisms that underlie the preferential specificity of CD4 T cells and have discovered that both intracellular events within antigen presenting cells, particular selective DM editing, and intercellular regulatory pathways, involving IFN-γ, indoleamine 2,3-dioxygenase and regulatory T cells, play a role in selecting the final peptide specificity of CD4 T cells. In this review, we summarize our findings, discuss the implications of this work on responses to pathogens and vaccines and speculate on the logic of these regulatory events.